Orchidophaga gastrodiacola Kato, 2006, is Chyliza vittata Meigen, 1826 (Diptera: Psilidae): discussion on its taxonomy and biology - Sueyoshi, Masahiro (Zootaxa, 2013)
Morphological features of a Japanese fly that developes in orchids, Orchidophaga gastrodiacola Kato, 2006, assigned to the family Scathophagidae, are reviewed and this species is proposed as a junior synonym of Chyliza vittata Meigen, 1826, of the family Psilidae. Morphological features of specimens from Japan correspond well with those from European. Japanese specimens of this transpalaearctic species utilize buds and stems of the achlorophyllous mycoheterotrophic Gastrodia elata Blume. This association is an exceptional habitat in comparisons to other congeners and European specimens of the same species.